PENGARUH KEPUASAN KERJA DAN MOTIVASI KERJA TERHADAP PRESTASI KERJA PEGAWAI PADA DINAS PERHUBUNGAN PROVINSI SUMATERA BARAT - Adek Putri; Helmi Prilla Aldino (LP2M Universitas Bina Bangsa, 2022)
This study aims to determine the effect of job satisfaction and motivation on the work performance of the Department of Transportation of West Sumatra Province employees. The sampling technique used in this study is the total sampling method using the entire population as a sample. The research sample is the Department of Transportation of West Sumatra Province employees. The total number of employees of the Department of Transportation of West Sumatra Province is 71. Data were collected by using questionnaires, observation, and literature study methods. The data analysis technique used instrument test, classical assumption test, multiple regression analysis, and hypothesis testing. The results showed that: (1) job satisfaction had a positive and significant effect on the work performance of the employees of the transportation department of West Sumatra province, and (2) work motivation had a positive and significant effect on the performance of the employees of the transportation service of the province of West Sumatra